Cooling Effect Efficiency Prediction of Aluminum Dimples Block using DOE Technique - N, Ganesan H.; S, Kasim M.; R, Izamshah; S, Anand T.J.; A, Hafiz M. S.; M, Nawi M.A.; B, Mohamed S. (International Journal of Engineering and Technology, 2018)
The main aim of the present work is to study the effect of heat enhancement method on the cooling process of a spherical dimple profile. It was prominently known that introducing dimples configuration causes an enhancement in heat transfer over a surface.Â In this project, an experimental investigation was carried out to examine the cooling effect of the spherical dimple profile during steady laminar flow in a wind tunnel. Seventeen different sets of parameters related to dimple diameter (mm), dimple orientation (angle) and air stream velocity (m/s) were studied. The Box-Behnken of Response Surface Methodology (RSM) was used as design of experiments (DoE) tool to evaluate these parameters on cooling time. This work deals with the analysis of variance (ANOVA) in order to establish the significant effect of input parameters. The result reveals that an increase in dimple diameter and air stream velocity increase heat dissipation. The shortest cooling time of 7 minutes can be achieved when the dimple diameter is 12 mm; the dimple orientation is 60Â° and air flow velocity at 18 m/s. The mathematical model has been rendered where the model has been experimentally validated with the average error of 6%.